2005
DOI: 10.1097/01.psy.0000160470.43167.e2
|View full text |Cite
|
Sign up to set email alerts
|

Can Subjective Asthma Symptoms Be Learned?

Abstract: Subjective respiratory symptoms can be learned in response to harmless stimuli and a substantial proportion of patients with asthma might be especially vulnerable to this phenomenon. Because asthma patients rely mainly on perceived symptoms for their medication use, it is likely that they will take reliever medication based on expected symptoms instead of real exacerbations of respiratory dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 48 publications
4
49
0
Order By: Relevance
“…However, the results correspond with previous findings which showed an influence of contextual variables on the perception of dyspnea [34]. In this regard, de Peuter et al [35] coupled dyspnea, induced by inhalation of CO 2 , with specifically labelled aerosols during training trials. In the following presentation of the labelled aerosols, which were then completely free of CO 2 , healthy and asthmatic participants reported more respiratory symptoms than during presentation of aerosols which have not been coupled with CO 2 inhalation during the preceding training trials.…”
Section: Discussionsupporting
confidence: 79%
“…However, the results correspond with previous findings which showed an influence of contextual variables on the perception of dyspnea [34]. In this regard, de Peuter et al [35] coupled dyspnea, induced by inhalation of CO 2 , with specifically labelled aerosols during training trials. In the following presentation of the labelled aerosols, which were then completely free of CO 2 , healthy and asthmatic participants reported more respiratory symptoms than during presentation of aerosols which have not been coupled with CO 2 inhalation during the preceding training trials.…”
Section: Discussionsupporting
confidence: 79%
“…In 2005, De Peuter et al (25) stated that overestimation of symptoms is associated with excessive use of medication and need for hospitalization. In 2008, Chapman et al (22) reported that patients who did not require urgent or specialist care were more likely to report shortterm symptom control of asthma than were those who required one or more emergency room visits.…”
Section: Discussionmentioning
confidence: 99%
“…This perception is modulated by past experience: the brain seems to memorize the level and the characteristics/quality of dyspnea induced by a previous activity, effort, or situation, to set the expectations accordingly, and ultimately compare the current input with that in the past [52,53]. It has been shown that, following conditioning, even harmless cues per se may trigger dyspnea with varying susceptibilities in different groups of individuals [54]. This reference is subject to changes at the conscious level using cognitive processes such as experience, learning, and interpretation [16,39,51].…”
Section: Neurophysiologymentioning
confidence: 99%
“…Previous experience and learning are two of the key factors influencing dyspnea [51,54]. Another one is negative affectivity, i.e., the general tendency to experience negative emotions and self-image, introversion, and dwelling on failures and shortcomings.…”
Section: General Therapeutic Principles Of Dyspneamentioning
confidence: 99%